Leveraging Artificial Intelligence to Enhance Digital Marketing : An Analysis of Best Practices and Future Directions - Hakobyan, Diana; Mareš, Jan, 1986-; Hron, Michal; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This master's thesis aims to comprehensively understand diverse AI models in digital marketing, empowering practitioners to enhance customer-brand engagement strategically. By bridging theory from the literature review and practical implementations from the in-depth expert interviews, it outlines specific AI tools, platforms, and applications, emphasizing advantages while addressing potential drawbacks. As a roadmap for future trends, the research examines ethical considerations, providing guidelines for responsible AI practices. The study concludes with practical recommendations to optimize AI adoption, contributing to advancing knowledge and aligning with global best practices in the field.
Vedoucí práce: Jan Mareš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses